Kedudukan Hukum Citizen Journalism (Jurnalis Warga Negara) Dalam Penyampaian Berita Kepada Masyarakat - Cokorda Gede Wirasatya Pradana; I Nyoman Putu Budiartha; I Wayan Arthanaya (Warmadewa Press, 2022)
Journalism is a profession whose duties are under the Press Law, if there is a problem in the process of delivering news, it is protected by the Press Council, in contrast to citizen journalism because it does not include legal protection intended for professional journalists. This study aims to analyze and describe the legal position and legal protection of citizen journalism in delivering news to the public. The study method used is normative legal research. The results show that the legal position of citizen journalism in delivering news to the public is almost the same as that of professional journalists because of its characteristics, but the legal umbrella for citizen journalism in Indonesia has not been clearly regulated. The legal protection of citizen journalism in delivering news to the public can be protected by the Press Law as long as it contains aspects of the public interest, education for the community, contains elements of 5W+1H, and based on the search process, and according to the principles of the journalistic code of ethics, protection can be provided.